2020
DOI: 10.2478/hukin-2020-0049
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activity Asymmetry of the Lower Limbs During Sprinting in Elite Soccer Players

Abstract: The analysis of movement patterns through EMG activity provides the opportunity to identify the muscle groups most involved in a particular exercise, and to determine the scope of inter-limb deficiencies. The aim of the present study was to investigate the effects of a side-to-side muscle activity asymmetry between the left and the right lower limb during sprinting in soccer players. Sixteen professional soccer players took part in the study. Their age, body mass and body height equaled 23.7 ± 7.6 years, 81.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, as the participants in this study were youth athletes (16.56 ± 1.93 years) without professional sprint training, inter-limb asymmetry of hamstring strength may impair sprint performance. During sprinting, the average activity in hamstring muscles was 33% greater in comparison to the quadriceps muscles, which meant that the greater involvement of hamstring muscles in this motor task ( Pietraszewski et al, 2020 ). Accordingly, we suggested that reducing the inter-limb asymmetry of hamstring strength may effectively enhance sprint performance by improving the efficiency of alternating limb movements, especially for the youth cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the participants in this study were youth athletes (16.56 ± 1.93 years) without professional sprint training, inter-limb asymmetry of hamstring strength may impair sprint performance. During sprinting, the average activity in hamstring muscles was 33% greater in comparison to the quadriceps muscles, which meant that the greater involvement of hamstring muscles in this motor task ( Pietraszewski et al, 2020 ). Accordingly, we suggested that reducing the inter-limb asymmetry of hamstring strength may effectively enhance sprint performance by improving the efficiency of alternating limb movements, especially for the youth cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the importance of lumbo-pelvic muscle function in the prevention and treatment of hamstring injuries has been proven, demonstrating how gluteus medius activation and strength during running has a high relationship with hamstring injuries [26]. Furthermore, it has been revealed that the greatest leg asymmetry (LA) between the right and left lower limbs occurs in the gluteal muscles and the least in the quadriceps [27]. The baseline versus post-training or change in LA between pre-and post-training was similar in the EG and CG, so it seems that this was not a determining factor for the difference between the number of injuries and injury burden in players who participated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the activation level and strength of the gluteus medius during high-speed running exhibit a strong correlation with hamstring injuries [26]. Furthermore, it has been shown that greater leg asymmetries are predominantly localized in the gluteal muscles [27]. These findings suggest that the hamstring and gluteal muscles may play crucial roles in strength training for soccer players, potentially averting injuries and enhancing physical performance [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from health complications, avoiding injuries is very important in preventing exclusion from game processes up to indefinite periods and reducing the performance of the team, as well as jeopardizing the player's career [1,2]. Soccer is characterized by rapid changes in the movement intensity and direction every 6 s, while most accidents lead to lower limb injury (71%) and occur more often (6-11 times) during matches than training [3][4][5][6]. The injury incidence has risen more than 4% in the last 17 years and may be due to increased game intensity over the past few decades [7,8], high and unpredictable opponent offensive and defensive activity (strategy), stress factors, maximal player efforts to engage in risky situations, or fatigue.…”
Section: Introductionmentioning
confidence: 99%